Digital Transformation in Public Policy during the New Order at the Regional Revenue and Management Agency of Sumedang Regency - Ii Sumantri (Global Writing Academica Researching and Publishing, 2022)
The Industrial Revolution 4.0 has brought significant changes in human life, including in dealing and working from manual to digital. Besides that, the existence of Covid-19 has also changed a new order of life which is called the new Normal. The Sumedang Regency Government at the Sumedang Regency Regional Revenue and Management Agency has responded to this challenge by implementing digital transformation in public policy by implementing an Electronic Based Government System (SPBE) policy through a service known as e-Office. This study aims to analyze the digital transformation of the Regional Revenue and Management Agency of Sumedang Regency. This research uses a qualitative approach with descriptive methods. The results of the study show that digital transformation of policies and public services at the Sumedang Regency Revenue and Management Agency has gone very well with the application of e-office. The application of e-office applications in addition to implementing several central and regional government policies, is also used as an internal service tool to assess the work of apparatus in carrying out basic tasks and functions individually . In this study it was also found that e-office applications still need to be developed between local governments and other parties with the concept of collaboration.